2007
DOI: 10.1038/sj.ejcn.1602857
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intervention to reduce the n−6/n−3 fatty acid ratio increases adiponectin concentration and fatty acid oxidation in healthy subjects

Abstract: Background/Objectives: Consumption of nÀ3 polyunsaturated fatty acids (PUFA) has a favourable impact on inflammation and cardiovascular disease. However, the Western diet is characterized by a low nÀ3 PUFA intake and an imbalance in the nÀ6/ nÀ3 PUFA ratio. Study the effect 10-week of diet modification to decrease the nÀ6/nÀ3 PUFA ratio on cardiovascular risk factors and resting energy expenditure. Conclusion: A decreased nÀ6/nÀ3 PUFA ratio can be achieved with simple dietary counselling, resulting in multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 44 publications
4
45
2
Order By: Relevance
“…It was also compatible with recent reports from the United Kingdom and France 16,17) . People in Japan consume more fish per capita than people in other countries; it has been reported that the median serum -3 PUFA concentration in Japanese people is much higher than in Caucasian and Japanese Americans 5,19) .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It was also compatible with recent reports from the United Kingdom and France 16,17) . People in Japan consume more fish per capita than people in other countries; it has been reported that the median serum -3 PUFA concentration in Japanese people is much higher than in Caucasian and Japanese Americans 5,19) .…”
Section: Discussionsupporting
confidence: 78%
“…In addition to these changes, the anti-atherosclerotic effect of fish was possibly due to the increased adiponectin concentration. In this study, the increment of the serum adiponectin concentration in response to fish consumption was relatively small, and was compatible with previous clinical trials 16,17,32) . It might be an important question whether this relatively small increase in adiponectin concentration could have any clinical meaning.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our observation is supported by Ramel et al (2009) who reported enhanced insulin sensitivity in individuals who were given fish oil (rich in long-chain omega-3 fatty acids) only if it was complemented with a calorie-restricted diet (that is, reduced saturated fat intake). Similarly, a 6-month hypocaloric lowfat combined with lean (white) fish diet altered the balance of saturated (reduced) and omega-3 (increased) fatty acids in the skeletal muscle membrane phospholipids in grossly obese/diabetic patients and this change was significantly associated with change in insulin sensitivity (Guebre-Egziabher et al, 2008). However, it is worth noting that despite the normalization of muscle membrane phospholipid fatty acid, the increased omega-3 fatty acids failed to lower the absolute concentration of circulating insulin.…”
Section: Discussionmentioning
confidence: 99%